Interaction of 2'-deoxyguanosine with cis-2-butene-1,4-dial: Computational approach to analysis of multistep chemical reactions - Sviatenko, L.K.; Gorb, L.G.; Hovorun, D.M.; Leszczynski, J. (Вiopolymers and Cell, 2014)
cis-2-Butene-1,4-dial represents a microsomal metabolite of furan, an industrially important chemical found in cigarette smoke, air pollution, and also in canned or jarred food. It is expected to be a human carcinogen. Aim. Investigation an effect of cis-2-butene-1,4-dial on the 2'-deoxyguanine which is a model of DNA site. Methods. Optimization of reaction species molecular structures, spectral parameters and Gibbs free energy calculations were performed using Gaussian09 program. Systems of differential equations for kinetics generation were solved using Mathcad15 program. Results. The predicted mechanism of the reaction of cis-2-butene-1,4-dial with 2'-deoxyguanine consists of four-step process formation of four diastereomeric primary adducts and further base-mediated five-step transformation of the primary adducts to the secondary one. The reaction kinetics, which allows defining theconcentration change of any reaction species was calculated. Conclusions. Under physiological conditions the interaction between cis-2-butene-1,4-dial and 2'-deoxyguanine leads to the formation of a stable adduct which could be responsible for the furan genotoxicity. цис-2-Бутен-1,4-діаль є мікросомним метаболітом фурану – промислово важливого хімікату, виявленого в сигаретному димі, забрудненому повітрі, а також, іноді, в консервованих або банкових продуктах. Його вважають потенційним канцерогеном для людини. Мета. Дослідити вплив цис-2-бутен-1,4-діалю на 2'-де- зоксигуанозин – модельний фрагмент ДНК. Методи. Оптимізацію структури учасників реакції, розрахунки спектральних параметрів і вільної енергії Гіббса виконано в програмі Gaussian09. Системи диференційних рівнянь для отримання кінетичних даних вирішували з використанням програми Mathcad15. Результати. Прогнозований механізм реакції цис-2-бутен-1,4-діалю з 2'-дезок- сигуанозином реалізується у чотири стадії, протягом яких утворюються чотири діастереоізомерних первинних адукти, та наступної п’ятистадійної трансформації, каталізованої основами, первинних адуктів у вторинні. Розраховано кінетику реакції, що дозволяє визначати зміни концентрації будь-якого учасника реакції. Висновки. За фізіологічних умов взаємодія між цис-2-бутен-1,4-діалем і 2'-дезоксигуанозином призводить до утворення стабільного адукта, який може відповідати за генотоксичність фурану. цис-2-Бутен-1,4-диаль является микросомным метаболитом фурана – промышленно важного химиката, обнаруженного в сигаретном дыме, загрязненном воздухе, а также, иногда, в консервированных или баночных продуктах. Его считают потенциальным канцерогеном для человека. Цель. Исследовать влияние цис-2- бутен-1,4-диаля на 2'-дезоксигуанозин – модельный фрагмент ДНК. Методы. Оптимизацию структуры участников реакции, расчеты спектральных параметров и свободной энергии Гиббса выполняли в программе Gaussian09. Системы дифференциальных уравнений для получения кинетических данных решали с помощью программы Mathcad15. Результаты. Реакция цис-2-бутен-1,4- диаля c 2'-дезоксигуанозином проходит в четыре стадии с формированием четырех диастереоизомерных первичных аддуктов и последующей, катализируемой основаниями, пятистадийной трансформации первичных аддуктов во вторичные. Рассчитана кинетика реакции, что позволяет определять изменения концентрации любого участника реакции. Выводы. При физиологических условиях взаимодействие между цис-2-бутен-1,4-диалем и 2'-дезоксигуанозином приводит к образованию стабильного аддукта, который может отвечать за генотоксичность фурана.